IS THERE A CONNECTION OF ANXIETY AS A PERSONALITY TRAIT WITH DEPRESSIVE PERSONALITY TRAITS? - Raspopovic, Milena (HEALTH CARE, 2021)
Introduction/aim. The results of previous research indicate that there is a connection between the symptoms of depression and anxiety, and that the occurrence of these symptoms is partly conditioned by personality traits. The aim of this study was to examine the correlation between anxiety as a personality trait and depressive personality traits among the respondents from Montenegro, in order to obtain guidance for the application of mental health programs. Method. The cross-sectional study included 355 respondents. Data were collected online, through the Google Forms platform In addition to the general questionnaire, questionnaires for the evaluation of anxiety-related traits and depressive personality traits (DP) were used. Results. Of 355 respondents, aged 18 to 68, 74.6% were women. A high positive correlation between the anxiety-related traits and depressive personality traits was significant (r = 0.82, p <0.01). In addition, we found that both of these traits were more pronounced in women, in respondents with lower educational levels and poorer material status. Younger respondents and unemployed persons had significantly more pronounced anxiety-related traits, but there was no significant difference regarding depressive personality traits. There was no significant difference regarding the pronounced anxious and depressive personality traits related to marital status and employment. Conclusion. Having in mind the fact that anxious and depressive personality traits occur simultaneously in a significant number of cases, it is important to detect these traits early and implement prevention programs in order to prevent them from developing into anxiety or depression.